Maskerade : a novel of Discworld - Pratchett, Terry (Pratchett, Terry. Discworld series., 2014)
The phantom in the bone-white mask who has haunted the Ankh-Morpork Opera House for years, is thought to be a benign presence until he starts killing performers backstage. Country girl Perdita X. hides in a chorus and has someone mime her aria solos so she may dodge the killing craze. She also uses this tactic to hide from her witchy relatives Nanny Ogg and old Granny Weatherwax who would rather she join their ranks. It all makes for a crazy and humorous show!